Pengaruh Tarif Layanan, dan Pendapatan Operasional Terhadap Profitabilitas Sebagai Intervening Variable Pada RS Bahagia - Adilah Rofifah Askari; Endang Winarsih; Sitti Zulaeha (Academic Bright Collaboration, 2024)
This research aims to determine how cost control has a significant effect on profitability with break even point as an intervening variable at Bahagia Hospital. To find out service rates have a significant effect on profitability with break even point as an intervening variable at Bahagia Hospital. To find out operational income has a significant effect on profitability with break even point as an intervening variable at Bahagia Hospital. The data collection method used is a questionnaire with quantitative data type. The research results show that (1) Partial test results (t test) show that cost control has a positive and significant effect on profitability. This is indicated by the calculated t score of 9.419 > t table 1.99 and a significant score of 0.000 < 0.05. (2) The results of the partial test (t test) show that service rates have a positive and significant effect on profitability. This is indicated by the calculated t score of -0.561 < t table 1.99 and a significant score of 0.577 > 0.05. (3) The results of the partial test (t test) show that operating income has a positive and significant effect on profitability. This is indicated by a calculated t score of 0.418 < t table 1.99 and a significant score of 0.678 > 0.05. (4) The results of the t test show that the hypothesis (Ha) is accepted and (H0) is rejected, which means that the variables of cost control, service rates, and operational income have a positive and significant effect on profitability with break even point as an intervening variable at Bahagia Hospital.